AN SOS ANALYTICAL WORKBENCH APPROACH TO ARCHITECTURAL ANALYSIS AND EVOLUTION. Issue 3 (6th October 2017) - DeLaurentis, Daniel; Davendralingam, Navindran; Marais, Karen; Guariniello, Cesare; Fang, Zhemei; Uday, Payuna
ABSTRACT: This article summarizes the development of a System of Systems Analytic Workbench (SoS AWB) that provides a set of computational tools to facilitate better‐informed decision‐making on evolving SoS architectures. The workbench motif is adopted since SoS practitioners typically generate archetypal technical queries that can be mapped to appropriate analysis methods best suited to provide outputs and insights directly relevant to posed questions. After an overview of the workbench framework, four distinct methods currently available for use are presented along with their distinctive aspects in the concept of use.